Budget impact analysis resulting from the use of dabigatran etexilate in preventing stroke in patients with non-valvular atrial fibrillation in Italy - Mennini, Francesco; Russo, Sergio; Marcellusi, Andrea (Farmeconomia. Health economics and therapeutic pathways, 2012)
Background: atrial fibrillation (AF) is the most common form of alteration in cardiac rhythm and associated with more severe episodes of stroke. Treatment with oral anticoagulants vitamin K antagonists (VKA) such as warfarin, is nowadays the therapy of choice for stroke prevention in patients with AF, but dabigatran etexilate (DE) 150 mg twice daily was more clinically effective than warfarin in reducing the risk of stroke or systemic embolism, ischaemic stroke and vascular mortality whereas DE 110 mg twice daily was non-inferior to warfarin. Aim: to assess the affordability of the use of DE for the Italian NHS, in patients with non-valvular AF (NVAF) through a budget impact analysis (BIA). Methods: the BIA in a timeframe of 5 years was divided into 3 scenarios (1: current management of patients with NVAF; 2: all patients with NVAF treated with VKA; 3: all patients with NVAF treated with DE). The population considered is the one with indication for anticoagulation. Analysis is from the NHS perspective: therefore, indirect costs are excluded. Results: the underuse of oral anticoagulation, associated with the difficulty in keeping the patients treated with VKA within an acceptable therapeutic range, results in an enormous social and human cost, represented by a total of more than 63,000 strokes cumulated in the 5-year period considered. The cumulative cost for the scenario 1 over the 5-year period is over € 2.3 billion. In the scenario 2 the number of strokes avoided per year increases by -5,219 compared to no treatment (-2,368 compared to scenario 1), although the number of events remains high (about 10,000 events/year). In the 5-year observation period the scenario 2 would result in a reduction in the total number of strokes (-12,323 events vs. scenario 1), and savings for the NHS of around 95 million Euros compared to scenario 1. In the Scenario 3 there is a reduction of more than 38,600 of the total cumulative number of strokes vs. the scenario 1 and over 26,200 vs. scenario 2, and savings for the NHS at the fifth year of observation of circa 174 million Euros vs. scenario 1 and 123 million Euros vs. scenario 2. Conclusion: DE in Italy is economically sustainable, as it allows savings for the NHS in the management of patients with NVAF from the second year vs. no treatment and vs. treatment with VKA